Molluscum contagiosum virus infection among PLWHA In Ibadan, Nigeria (2014)
Background: Molluscum contagiosum (MC) infection is caused by a pox virus and the virus is probably passed on by direct skin-to- skin contact which may affect any part of the body. There is anecdotal evidence associating facial lesions with HIV-related immunodeficiency. This study was aimed to determine the prevalence and associated risk factors of Molluscum contagiosum infection among PLWHAs attending ART clinic at the University College Hospital, Ibadan, Nigeria. Methods: This is a descriptive cross-sectional survey of 5,207 patients (3519 female and 1688 males) attending ART clinic between January 2006 and December 2007. Physicians performed complete physical and pelvic examinations. Diagnosis of Molluscum Contagiosum infection was based on the clinical findings of typical lesions on the external genitalia, perianal, trunk, abdominal and facial regions. Results: The mean age of the patients was 34.67 yrs. ± 9.16). About 10% (542) had various sexually transmitted infections (STIs). The male to female ratio was 1: 4.2. One hundred and twenty seven subjects (23.4%) had no formal or primary education with 247 (45.6 %) being treatment naive while 295 (54.4 %) were treatment experienced. Of the 542 PLWHAs with STIs, 3.3 % had undetectable viral load (< 200 copies/ ml) while 272 (50.1 %) had low CD4 count (< 200 cells / mm3.) and The Mean log10 viral load was 5.02 ± 0.94. Molluscum Contagiosum infection was diagnosed in 13 patients (0.024%; 8 females and 5 males). Vaginal Candidiasis was the commonest genital infection diagnosed in 223 (41.1%) of the patients with STIs. MC patients had higher viral load, lower CD4 count and more likely to be treatment experienced”. Conclusions: Molluscum Contagiosum infection is not uncommon among the HIV-infected patients, but underreported. Awareness of this cutaneous manifestation should be known to Physicians in AIDS care.